1999
DOI: 10.1046/j.1365-8711.1999.03085.x
|View full text |Cite
|
Sign up to set email alerts
|

On the parallax of WD 0346+246: a halo white dwarf candidate

Abstract: We present a parallax measurement for the very cool degenerate WD 0346+246, the serendipitous discovery of which was reported by Hambly et al. We find an absolute parallax of 36±5 mas, yielding a distance estimate of 28±4 pc. The resulting absolute visual magnitude of the object is MV=16.8±0.3, making it the second‐lowest luminosity white dwarf currently known. We use the distance estimate and measured proper motion to show that the object has kinematics consistent with membership of the Galactic halo. WD 0346… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Therefore WD0346+246 does not have a high mass (like ESO439-26 25 ) and is probably a`normal', albeit unusually cool, white dwarf. The location of WD0346+246 on the white-dwarf sequence in the M V , V±I diagram also supports this argument 21 . Estimating the age of WD0346+246 is dif®cult, as we lack important information concerning the atmosphere and core composition.…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Therefore WD0346+246 does not have a high mass (like ESO439-26 25 ) and is probably a`normal', albeit unusually cool, white dwarf. The location of WD0346+246 on the white-dwarf sequence in the M V , V±I diagram also supports this argument 21 . Estimating the age of WD0346+246 is dif®cult, as we lack important information concerning the atmosphere and core composition.…”
supporting
confidence: 63%
“…Using the distance to WD0346+246 given in ref. 21, we ®nd L 7:6 6 2:3 3 10 28 erg s 2 1 , or L 2:0 6 0:6 3 10 2 5 L ( , and r 0:012 6 0:002R ( (here L ( and R ( are the solar luminosity and radius, respectively). The models 24 indicate a mass of 0:65 6 0:15M ( .…”
mentioning
confidence: 98%
“…Hambly et al (1999), Dahn et al (2002), Tinney et al (2003), and Vrba et al (2004) have reported a total of one, one, two, and five first trigonometric parallaxes for MOTION systems, respectively. All of those studies concentrated on the (very) cool end of the main sequence, L or T dwarfs, or in a single case, a white dwarf.…”
Section: Discussionmentioning
confidence: 98%
“…The challenge is the need for a largescale parallax survey focusing on WDs to confirm proximity. Since the Hipparcos mission, only six WD trigonometric parallaxes have been published (Hambly et al 1999;Smart et al 2003), and of those, only two are within 25 pc. The USNO parallax program is in the process of publishing trigonometric parallaxes for $130 WDs, mostly in the northern hemisphere, although proximity was not a primary motivation for target selection (C. Dahn 2004, private communication).…”
Section: Discussionmentioning
confidence: 99%